Board Attributes and Financial Risk Management: Moderating effect of Ownership Structure among Listed Non-Financial Firms in Kenya - Tarus , T. K.; Komen , J.; Tenai , J. K. (African Journal of Education,Science and Technology (AJEST), 2019)
Markets have been distinguished by accelerated uncertainty of interest rates, foreign exchange rates, the volatility of security prices as well as fluctuations of commodity prices and, as a result, businesses face rapid vulnerability towards a broad array of corporate risks. The study aimed to examine whether ownership structure moderates the connection between board attributes and financial risk management. The target population was 67 listed firms in Kenya while the sample included 41 non-financial companies based on inclusion-exclusion criteria from 2010-2017 giving a total of 328 firm-year observation. The hierarchical binary logistic regression was utilized to evaluate the interaction conditions of the hypothesis. The findings of the research revealed that the ownership structure had a positive and insignificant moderating effect on the connection between financial expertise of the board and financial risk management (ß=0.12, ρ>0.05) while independent board members and financial risk management were positively and significantly moderated by ownership structure (β=0.75, ρ<0.05). The study concludes that board financial expertise is a key determinant of boards’ ability to make firm strategic decisions while a high proportion of outside directors was detrimental to hedging activities whereas ownership structure enhanced the relationship. The study findings will be useful to investors who want to make investments in firms by understanding board attributes in relation to risk management. This research offers logical information, especially in for emerging economies on the role of ownership structure in influencing financial risk management decisions.